2004
DOI: 10.1037/0033-2909.130.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Measuring Personality Vulnerability to Depression: Comment on Coyne and Whiffen (1995).

Abstract: J. C. Coyne and V. E. Whiffen (1995) reviewed research on personality vulnerability to depression, focusing on S. J. Blatt's (1974, 1990) concepts of dependency and self-criticism and A. T. Beck's (1983) concepts of sociotropy and autonomy. The authors discuss 6 issues raised in that review: (a) the typological or dimensional nature of vulnerability, (b) the theoretical implications of "mixed" vulnerability, (c) the relations of vulnerability to Neuroticism. (d) the potential confounding of vulnerability with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
336
4
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(381 citation statements)
references
References 177 publications
(384 reference statements)
36
336
4
5
Order By: Relevance
“…The items loading on the second DEQ factor, Self-Criticism, reflect a continuous preoccupation with failure, ambivalent feelings about self and others, and a self-critical stance (Blatt et al, 1974). A considerable body of research has demonstrated that Self-Criticism as compared to Dependency involves greater vulnerability to depression as well as to other negative affects and distress (e.g., Besser, 2004;Besser, Flett, & Davis, 2003;Besser & Priel, 2003;Besser & Priel, 2005a, 2005bBlatt, 2004;Luyten, Corveleyn, & Blatt, 2005;Nietzel & Harris, 1990;Zuroff, Mongrain, & Santor, 2004).…”
Section: Blatt's Two Primary Configurations Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The items loading on the second DEQ factor, Self-Criticism, reflect a continuous preoccupation with failure, ambivalent feelings about self and others, and a self-critical stance (Blatt et al, 1974). A considerable body of research has demonstrated that Self-Criticism as compared to Dependency involves greater vulnerability to depression as well as to other negative affects and distress (e.g., Besser, 2004;Besser, Flett, & Davis, 2003;Besser & Priel, 2003;Besser & Priel, 2005a, 2005bBlatt, 2004;Luyten, Corveleyn, & Blatt, 2005;Nietzel & Harris, 1990;Zuroff, Mongrain, & Santor, 2004).…”
Section: Blatt's Two Primary Configurations Modelmentioning
confidence: 99%
“…It seems that the magnitude of situational demands do not directly determine the expression of symptoms of stress because individual differences in coping abilities and vulnerabilities may have a magnifying impact among individuals (the accentuation principle), underscoring the need to investigate the interactions between the environment and the person as an active agent (Luyten, Blatt, Van Houdenhove, & Corveleyn, 2006;Shahar, 2006;Zuroff, Mongrain, & Santor, 2004).…”
Section: The Transition To Motherhood and Postpartum Depression In Thmentioning
confidence: 99%
“…Research has shown that these general mental representations are also associated with different relational styles (for reviews, see Blatt, 2004;Luyten et al, 2005;Zuroff et al, 2004). Briefly, self-critical individuals tend to avoid intimate relationships, and once a relationship is established they remain distrustful and dissatisfied (Blatt and Zuroff, 1992;.…”
Section: Self-criticism Dependency and Romantic Relationshipsmentioning
confidence: 99%
“…They can be used to assess (a) prevalence rates of risk factors presumed to produce these disorders in various segments of the population (e.g., overemphasis on individual achievement at the expense of social connectedness) and (b) comorbid traits and experiences (e.g., perfectionism, stressful life events) that are presumed to exacerbate these underlying risk factors (see Zuroff, Mongrain, & Santor, 2004).…”
Section: Epidemiological Studiesmentioning
confidence: 99%